Can kinematics, file diameter, and PUI influence the intracanal decontamination and apical bacterial extrusion? - Maricel Rosario Cardenas Cuellar; Evelyn Giuliana Velásquez-Espedilla; Victor Feliz Pedrinha; Rodrigo Ricci Vivan; Marco Antonio Hungaro Duarte; Flaviana Bombarda de Andrade
Abstract: The present study investigated the intracanal decontamination and apical extrusion of bacteria and debris from root canals instrumented with rotary and reciprocating systems (ProDesign Logic or ProDesign R), with different file diameters and using conventional syringe irrigation (CSI) or passive ultrasonic irrigation (PUI). Eighty extracted mandibular premolars were contaminated with Enterococcus faecalis and randomly assigned to eight experimental groups according to the root canal instrumentation and irrigation technique employed (n = 10): G1: Prodesign Logic 25.06; G2: Prodesign R 25.06; G3 and G4 were instrumented with the same single-file systems, respectively, using 35.05 diameters and CSI. G5, G6, G7, and G8 were instrumented like the previous groups, but with PUI. Apically extruded debris during instrumentation was collected into pre-weighed microtubes. The weight of the empty microtube was subtracted from the final weight to establish the amount of extruded debris. Bacteria from root canals and extruded debris were collected for a microbiological evaluation of colony forming units (CFU/mL). For statistical analyses, the Mann-Whitney and Kruskal-Wallis followed by the Dunn's tests were used (α = 0.05). All instruments caused extrusion of debris. For irrigation techniques, PUI promoted greater debris and bacterial extrusion (p < 0.05). The CFU/mL count indicated that the instrumentation of the experimental groups were equally effective in the decontamination of the root canal (p > 0.05). The systems tested (regarding file diameter and kinematics) were associated with similar amounts of apically extruded debris and root canal decontamination. PUI was associated with greater debris and bacterial extrusion.